Effect of organic and Biofertilizers application on yield of Nigella Sativa L. plant - Nassif, Anwar Hussein; Al-Zubaidy, Najm Abdullah Jumaa; Abd, Rabab Majead (Journal of agricultural, environmental and veterinary sciences, 2023)
A field experiment was carried out in one of the agricultural fields in the Al-Tahweela district in Al-Khalis city, Diyala Governorate, Iraq, which is located 16 km northeast of Baqubah, during the autumn season of the year 2021, in soil with a clay texture. Two-factors experiment was carried out according to the randomized complete block design (RCBD) with three replications. The first factor, Trichodermia harzianum, was added or not at a concentration of 0.3 gm. The second factor included four levels of humic acid: 0, 2, 4, and 6. gm.m-2 The results of the experiment showed the following: The addition of humic acid excelled at the level of 6 g. m-2 was significant by giving the highest averages in the number of cans. Plant-1, 1000 seeds weight, the yield of plant, and the total yield. Trichoderma Application gave the highest averages for each of the number of cans. Plant-1, weight of 1000 seeds, yield of plant, and the total yield, respectively, compared to Untreated control treatment Which gave the lowest.